Analisis Kebijakan Penurunan Angsuran Pajak Penghasilan Pasal 25 Di Masa Pandemi Covid 19 Di Tahun 2020-2021 (Studi Kasus Pada Kantor Pelayanan Pajak Pratama Jakarta Pademangan) - Aning Nabilla; Bambang Irawan (Institut Ilmu Sosial dan Manajemen STIAMI, 2023)
Policy of decreasing corporate income tax installments through Perppu Number 1 of 2020 is one of the tax incentives provided government to corporate taxpayers as a form of coping with the pandemic Covid-19 to ease tax obligations in recovery efforts national economy. The purpose of this study was to analyze how policy implementation of income tax installment reduction Article 25, barriers and efforts made in KPP Pratama Jakarta Pademangan. This research using qualitative research methods with the aim of analyzing and describe the implementation based on Kapioru theory (2014). Results from research is the implementation of policies to reduce income tax installments Article 25 has gone well, and without obstacles so that no efforts that need to be made in its application, Policy Implementation the decrease in installments must be done consistently and continuously by taking into account the goals and objectives appropriate in accordance with Perppu No. 1 Year 2020.